In-situ synthesis of Ge/Ti4O7 composite with enhanced electrochemical properties. Issue 1 (January 2018) - Choe, Hui-Seon; Kim, Min-Cheol; Moon, Sang-Hyun; Kim, Eun-Soo; Kim, Si-Jin; Lee, Gyu-Ho; Won, Ji-Eun; Park, Kyung-Won
Abstract: Germanium (Ge) is a high-capacity material that has been extensively studied due to its relatively high theoretical capacity, excellent electrical conductivity, and high Li diffusion coefficient. However, to overcome the severe volumetric expansion of Ge caused by the alloy/dealloy process during cycling, composite structures consisting of Ge and a highly stable 2nd material need to be developed. In this study, a composite structure consisting of Ge and Ti4 O7 (Ge/Ti4 O7 ) is prepared using a facile, in-situ process with GeO2 and TiO2 under an H2 atmosphere at 900 °C. Ge/Ti4 O7 exhibits a relatively small particle size of < 1 µm compared to pure Ge (> 10 µm) prepared in the absence of TiO2 . Ge/Ti4 O7 as an anode for LIB shows a highly reversible capacity and enhanced cycling performance compared to pure Ge electrode. The enhanced electrochemical properties of Ge/Ti4 O7 might be attributed to Ti4 O7 acting as an electronically conductive matrix in the composite, which could buffer the pulverization of Ge during the cycle.